HETEAC-Flex model: comparative evaluation of six forward model configurations for dust cases using ground-based Lidar observations in Limassol - Savva, Athina; Nisantzi, Argyro; Poutli, Maria; Ansmann, Albert; Hadjimitsis, Diofantos G.; Mamouri, Rodanthi-Elisavet (My University, 2025)
The Cyprus Atmospheric Remote Sensing Observatory National Facility (CARO NF) of Eratosthenes Centre of Excellence plays a key role in atmospheric research and the characterization of atmospheric conditions in the Eastern Mediterranean. Equipped with cutting-edge remote sensing instruments including a PollyΧΤ Polarization Raman Lidar, a Cloud Radar and a Solar Infrastructure, CARO provides critical observations for studying aerosol properties, cloud dynamics, and radiative processes. Its advanced capabilities make it an essential ground-based station for satellite validation studies, particularly in the context of the EarthCARE mission (ESA/JAXA). To ensure compatibility between ground-based observations and satellite measurements, the HETEAC-Flex model, introduced by A. A. Floutsi et al., 2024 [1] have been applied for the aerosol layer classification. This model was created to validate the aerosol classification of ATLID (ATmospheric LIDar) measurements, onboard EarthCARE, by providing a robust comparison framework. Based on an Optimal Estimation Method (OEM) HETEAC-Flex provides six forward retrieval modes, each incorporating different sets of optical properties including Particle linear depolarization ratio at 355, 532 nm, Lidar ratio at 355, 532 nm, Extinction-related Ångström exponent at 355/532 nm and the Backscatter-related color ratio for 532/1064 nm. The typing scheme enables the identification of four aerosol components of aerosol mixtures, absorbing and less-absorbing fine-mode particles and spherical and non-spherical coarse-mode particles (FSA, FSNA CS, CNS, respectively). CARO’s PollyΧΤ lidar in Limassol can retrieve all the optical properties needed for the utilization of all the six retrieval modes. In this study, we apply the HETEAC-Flex model to several dust cases recorded in Limassol between the period 2021-2024, aiming to determine which retrieval mode is the optimal for the characterizing dust aerosol layers.
Keywords: HETEAC-Flex; Dust Cases; Aerosol Characterization; Lidar; Limassol